Odpowiedzi

Najlepsza Odpowiedź!
2010-03-23T19:51:17+01:00

a)a= 6cm b= 3cm c= 9cm
V=a*b*c
V=6*3*9=162cm³
Pc=2(a*b+b*c+c*a)
Pc= 2(6*3+3*9+9*6)
Pc= 198cm(kwadratowe)

b) a= 6dm b= 60 cm c= 4,2 dm
b=60cm=6dm
V=6*6*4,2=151,2dm³
Pc=2(6*6+6*4,2+4,2*6)=172,8dm(kwadratowych)

c)a= 2m b= 0,4 m c= 2,8 m
V=2*0,4*2,8=2,24m³
Pc= 2(2*0,4+ 0,4*2,8+ 2,8*2)= 15,04m(kwadratowych)
2 4 2
2010-03-23T19:55:14+01:00
A)a= 6cm b= 3cm c= 9cm
V=a*b*c
V=6*3*9=162cm³
Pc=2(a*b+b*c+c*a)
Pc= 2(6*3+3*9+9*6)
Pc= 198cm(kwadratowe)

b) a= 6dm b= 60 cm c= 4,2 dm
b=60cm=6dm
V=6*6*4,2=151,2dm³
Pc=2(6*6+6*4,2+4,2*6)=172,8dm(kwadratowych)

c)a= 2m b= 0,4 m c= 2,8 m
V=2*0,4*2,8=2,24m³
Pc= 2(2*0,4+ 0,4*2,8+ 2,8*2)= 15,04m(kwadratowych)
1 4 1
2010-03-23T19:55:27+01:00
A) P= 2ab + 2bh + 2ah
takim wzoremm rozwiązuj zadania!
1 2 1